The television advertising framework in Malaysia and the salience of ideals for Malay Muslims and Malaysians: a framing perspective for nation building - Mokhtar, Aida (Universiti Kebangsaan Malaysia Press, 2018)
Malaysia has the ambition to be a developed country by 2020. The goal of creating a cohesive, united, and ethical community is accentuated in the country’s Eleventh Malaysia Plan that is part of the nation’s endeavour in becoming a developed nation. There are several guidelines and codes issued by government organisations that regulate or encourage the self-regulation of television advertisements in Malaysia. This study uses framing theory that, according to the literature, refers to the attributes selected on a particular issue that form a narrative making them more salient than others. Framing theory is often used in studies on news stories. This study took on a different stance as it examined the television advertising regulatory framework in Malaysia instead of news stories. There is a research gap with the dearth of previous studies on regulations, culture, religion and framing. The study was with the aim of identifying frames that represent Malaysian and Malay Muslim values. It is a significant study as it contributes to current literature, uncovers how the government guides television advertising for the diverse Malaysian audience and provides a better understanding of the framework in relation to nation building in Malaysia. Five frames were generated from the framework examined and evidence was gathered from the Qur’an and Sunnah. The study finds that the frames generated represent the balance between the moral and material dimensions of life underscoring the concept of wasatiyyah that defines the moderate lifestyle in Islam.